2006
DOI: 10.2353/jmoldx.2006.060077
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Testing in Uveal Melanoma by Transcriptomic Profiling of Fine Needle Biopsy Specimens

Abstract: Many uveal melanoma patients die of metastasis despite ocular treatment. Transcriptomic profiling of enucleated tumors can identify patients at high metastatic risk. Because most uveal melanomas do not require enucleation, a biopsy would be required for this analysis. Here, we establish the feasibility of transcriptomic analysis of uveal melanomas from fine needle aspirates. Transcriptomic profiles were analyzed from postenucleation "mock" needle biopsies and matching tumors from eight enucleated eyes and from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 8 publications
(13 reference statements)
0
64
0
Order By: Relevance
“…We have shown previously that our RNA-based classifier is a more accurate prognostic indicator than monosomy 3 or clinicopathologic factors in uveal melanoma (13,18). Nevertheless, we recognized the need to develop a DNA-based assay both as a supplement to the RNA-based classifier and as an alternative when RNA of sufficient quality for expression profiling is not available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown previously that our RNA-based classifier is a more accurate prognostic indicator than monosomy 3 or clinicopathologic factors in uveal melanoma (13,18). Nevertheless, we recognized the need to develop a DNA-based assay both as a supplement to the RNA-based classifier and as an alternative when RNA of sufficient quality for expression profiling is not available.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the tumors in this study were analyzed previously by microarray gene expression profiling, dual-color FISH, and/or aCGH (13,17,18). Therefore, we were able to compare the SNP-based LOH assay with these other molecular techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Starting a little over a decade ago, investigators around the world began to report that chromosomal and transcriptional features of primary uveal melanoma cells were strongly associated with the pa tient's likelihood of developing subsequent extraophthalmic metastasis and metastatic death (25,(29)(30)(31)(32)(33)(34)(35) Several authors have shown that these chromosomal and transcriptional features can be determined on tumor specimens obtained by FNAB changing the indication for FNAB from purely diagnostic to investigational-prognostic (24,25,(36)(37)(38) . During the past few years, investigators from several of these centers have reported their experience with cytogenetic testing of the obtained FNAB aspirates (25,27,35,37,(39)(40)(41) .…”
Section: Prognostic Implications Of Cytopathologic Classification Of mentioning
confidence: 99%
“…During the past few years, investigators from several of these centers have reported their experience with cytogenetic testing of the obtained FNAB aspirates (25,27,35,37,(39)(40)(41) . In some of these centers, the results of FNAB are already being used clinically to inform patients of their metastatic risk, direct surveillance testing for metastasis, and even identify high risk subgroups for possible future recruitment into clinical trials of adjuvant therapies intended to prevent or delay the onset of metastasis (25,35,40,42) However, in most reported studies of investigational-prognostic testing of uveal melanomas sampled by FNAB, cytopathologic diagnosis of the obtained tumor cells has not been reported.…”
Section: Prognostic Implications Of Cytopathologic Classification Of mentioning
confidence: 99%
“…Both monosomy 3 analysis using the microsatellite DNA assay and transcriptome profiling have been successfully performed in fine-needle biopsy uveal melanoma specimens taken prior to radiotherapy, and CISH has been shown to work successfully on fine-needle biopsies from breast and lung cancer patients. [28][29][30][31] Previous studies 16,17,23 have shown epithelioid cells to correlate with loss of 1 copy of chromosome 3. In our study, monosomy 3 was detected in 38% of the epithelioid/mixed cell types (Table 5).…”
Section: Commentmentioning
confidence: 99%